Engineered T Cell Therapy for Gynecologic Malignancies: Challenges and Opportunities - Xu, Yifan; Jiang, Jin; Wang, Yutong; Wang, Wei; Li, Haokun; Lai, Wenyu; Zhou, Zhipeng; Zhu, Wei; Xiang, Zheng; Wang, Zhiming; Zhu, Zhe; Yu, Lingfeng; et al. (Frontiers in Immunology, 2021)
Gynecologic malignancies, mainly including ovarian cancer, cervical cancer and endometrial cancer, are leading causes of death among women worldwide with high incidence and mortality rate. Recently, adoptive T cell therapy (ACT) using engineered T cells redirected by genes which encode for tumor-specific chimeric antigen receptors (CARs) or T cell receptors (TCRs) has demonstrated a delightful potency in B cell lymphoma treatment. Researches impelling ACT to be applied in treating solid tumors like gynecologic tumors are ongoing. This review summarizes the preclinical research and clinical application of engineered T cells therapy for gynecologic cancer in order to arouse new thoughts for remedies of this disease.